Marlowe [videorecording (DVD)] - Jordan, Neil, 1950-; Monahan, William; Holmes, David, 1969-; Neeson, Liam; Kruger, Diane, 1976-; Lange, Jessica; Akinnuoye-Agbaje, Adewale, 1967-; Hart, Ian, 1964-; Meaney, Colm, 1953-; Melchior, Daniela, 1996-; Arnaud, François, 1985-; Kerslake, Seána; et al. (Universal Studios, 2023)
"A gripping noir crime thriller set in late 1930s Bay City centers around a brooding, down-on-his-luck detective; Philip Marlowe, played by Liam Neeson, who is hired to find the ex-lover of a glamorous heiress, daughter of a well-known movie star. The disappearance is the first twist in a series of bewildering events, and soon Marlowe is embroiled in a deadly investigation and web of lies that he's determined to bring to light." --